Fungal endophyte infection of ryegrass reprograms host metabolism and alters development. Issue 4 (25th August 2015) - Dupont, Pierre‐Yves; Eaton, Carla J.; Wargent, Jason J.; Fechtner, Susanne; Solomon, Peter; Schmid, Jan; Day, Robert C.; Scott, Barry; Cox, Murray P.
Summary: Beneficial associations between plants and microbes play an important role in both natural and agricultural ecosystems. For example, associations between fungi of the genus Epichloë, and cool‐season grasses are known for their ability to increase resistance to insect pests, fungal pathogens and drought. However, little is known about the molecular changes induced by endophyte infection. To study the impact of endophyte infection, we compared the expression profiles, based on RNA sequencing, of perennial ryegrass infected with Epichloë festucae with noninfected plants. We show that infection causes dramatic changes in the expression of over one third of host genes. This is in stark contrast to mycorrhizal associations, where substantially fewer changes in host gene expression are observed, and is more similar to pathogenic interactions. We reveal that endophyte infection triggers reprogramming of host metabolism, favouring secondary metabolism at a cost to primary metabolism. Infection also induces changes in host development, particularly trichome formation and cell wall biogenesis. Importantly, this work sheds light on the mechanisms underlying enhanced resistance to drought and super‐infection by fungal pathogens provided by fungal endophyte infection. Finally, our study reveals that not all beneficial plant–microbe associations behave the same in terms of their effects on the host.